The relationship between c-reactive protein and cardiovascular events in patients with obstructive and nonobstructive coronary artery disease - Hui-Wen Zhang; Yuan-Lin Guo; Cheng-Gang Zhu; Na-Qiong Wu; Ying Gao; Qian Dong; Jing Sun; Jian-Jun Li (Cardiology Plus, 2021)
Background and Objectives: Patients with nonobstructive coronary artery disease (NOCAD) have an increased risk of cardiovascular events (CVEs) compared to that in individuals with normal or near-normal coronary arteries (NNCAs) and even a similar risk to that in individuals with obstructive coronary artery disease (OCAD). However, the predictors for a worse outcome in patients with NOCAD are not fully determined. This study aimed to investigate the association of high-sensitive C-reactive protein (hs-CRP) and CVEs in patients with NOCAD. Materials and Methods: In total, 4662 patients with coronary artery angiography were enrolled and followed up for CVE. Patients were classified as having NNCA (<20% stenosis, n = 698, 15.0%), NOCAD (20%–49% stenosis, n = 639, 14.3%), and OCAD (≥50% stenosis, n = 3325, 70.7%) and then further subdivided into three groups based on their baseline hs-CRP level (<1, 1–3, and >3 mg/L). Proportional hazards models were used to assess the risk of CVEs. Results: Over an average 13403 person-year follow-up, 338 patients experienced CVEs. Patients with NOCAD and OCAD had a higher rate of CVE than those with NNCA (P < 0.05). The CVE risk was significantly higher in NOCAD (hazard ratio [HR]: 2.31, 95% confidence interval [CI]: 1.30–4.01, P = 0.004) and OCAD (HR: 3.09, 95% CI: 1.88–5.07, P < 0.001) patients than in NNCA patients. Moreover, elevated hs-CRP levels were associated with an incremental rate of CVE (P < 0.05). Conclusions: Patients with NOCAD had worse outcomes and elevated hs-CRP levels were positively associated with CVEs, which potentially helps assess risk in NOCAD patients.